2015
DOI: 10.3109/10582452.2015.1132026
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Neck and Shoulder Symptoms and Associations with Comorbidities and Disability: The Johnston County Osteoarthritis Project

Abstract: Objectives Neck and shoulder pain are common but underreported by older people, raising important questions of frequency, medical comorbidities, gender and racial disparities and functional impact associated with neck and shoulder symptoms in elders, which we examined in this analysis. Methods We performed a cross-sectional analysis in the community-based Johnston County Osteoarthritis Project, a cohort that is representative of the U.S. population, utilizing data from 1672 participants with a mean age of 68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
(63 reference statements)
1
18
0
Order By: Relevance
“…Regarding NP, previous studies on the relationship between NP and DM have yielded conflicting results. 12 , 16 , 17 Our results agree with Molsted et al, 15 who compared 951 patients with type 2 DM with data for 2,923 matched subjects from the general population and observed that patients with type 2 DM had a significantly higher prevalence of musculo-skeletal pain in all areas of the body, including cervical pain. In the US, using the 2002 National Health Interview Survey, it was found that the 3-month prevalence rate of back and/or NP had a significant association with concomitant LBP and NP for people with DM.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Regarding NP, previous studies on the relationship between NP and DM have yielded conflicting results. 12 , 16 , 17 Our results agree with Molsted et al, 15 who compared 951 patients with type 2 DM with data for 2,923 matched subjects from the general population and observed that patients with type 2 DM had a significantly higher prevalence of musculo-skeletal pain in all areas of the body, including cervical pain. In the US, using the 2002 National Health Interview Survey, it was found that the 3-month prevalence rate of back and/or NP had a significant association with concomitant LBP and NP for people with DM.…”
Section: Discussionsupporting
confidence: 90%
“…However, in the Johnston County Osteoarthritis Project, neck and shoulder symptoms were associated with DM; however, the association between DM and NP was not significant after full adjustment. 17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological studies have suggested that the prevalence of neck pain is 6-22% and 7-27% for shoulder pain (79). The Global Burden of Disease Study 2010 found that of the 291 conditions studied, neck or shoulder pain as a single entity ranked 21st in overall burden on society, and 4th in terms of overall disability (8).…”
Section: Introductionmentioning
confidence: 99%